Identifikasi Escherichia coli dan Salmonella spp pada Karkas Sapi di Rumah Potong Hewan di Banyuwangi dan Resistensi Terhadap Antibiotika - Faisal Fikri; Muhammad Thohawi Elziyad Purnama; Amung Logam Saputro; Iwan Sahrial Hamid (Fakultas Kedokteran Hewan Universitas Gadjah Mada bekerjasama dengan PB PDHI, 2018)
Food borne disease can be transmitted through Escherichia coli and Salmonella spp contamination. The contamination of microorganisms with high pathogenic potentials on bovine carcasses results in food borne illness. The aim of this study was to identify multidrug-resistance of Escherichia coli and Salmonella spp on carcass samples that isolated from slaughter house in Banyuwangi. Samples were collected from district of Banyuwangi, Rogojampi, Genteng and Kalibaru. This study used cross sectional study with assumption of prevalence at 50% in each contaminant, confidence level 95% and standart of error at 10%. By the number of samples should reach 96 samples. The result showed that seven samples (7,3%) were positive Escherichia coli and none samples (0%) were positive Salmonella spp. The multidrug-resistance of Escherichia coli showed that Cephalotin (42,9%), Trimethoprim (14,3%) and Erythromycin (42,9%) whereas Ampicillin, Enrofloxacin, Chloramphenicol and Tetracycline were sensitive against Escherichia coli.